The Development of Learning Activities Packages based on Creativity-Based Learning Entitled Basic Economic Problems, Social Studies, Religion and Culture Learning Substance Group for Prathomsuksa 6 students: Learning activity packages, Creativity-Based Learning - จอมหงษ์พิพัฒน์, ภูมิพงษ์ (Ubon Ratchathani Journal of Research and Evaluation, 2024)
The objectives of this research are 1) to develop the learning activities packages based on creativity-based learning entitled basic economic problems, social studies, religion and culture learning substance group for prathomsuksa 6 students to be effective according to the criterion 80/80 2) To compare achievement before and after studying with the learning activities packages based on creativity-based learning 3) To assess the satisfaction of prathomsuksa 6 students with learning Using the learning activities packages. The sample is prathomsuksa 6 students at Ban Pladuk School Under the Ubon Ratchathani Primary Educational Service Area Office, Area 1, Semester 1, 1/2023, a total of 30 students were obtained by cluster random sampling. The tools used in the research were: 1) the learning activities packages 2) learning achievement tests. It is a multiple choice type with 4 options. 3) Satisfaction questionnaire with a 5 level rating scale. The research findings were as follows: . 1. the learning activities packages based on creativity-based learning has efficiency equal to 88.13/87.00 which higher the specified criteria Academic achievement After studying higher than before studying It is statistically significant at the .01 level. prathomsuksa 6 students 6 students are satisfied with learning with the overall learning activity packages at a high level has an average of 4.22 and standard deviation 0.89.